The Efficacy and Safety of Tirzepatide in Patients with Diabetes and/or Obesity: Systematic Review and Meta-Analysis of Randomized Clinical Trials - Ligang Liu; Hekai Shi; Merilyn Xie; Yuxiao Sun; Milap C. Nahata (Pharmaceuticals)
Background: Obesity and type 2 diabetes (T2D) are major public health concerns. Tirzepatide has shown promise in recent clinical trials. This systematic review and meta-analysis aim to evaluate the efficacy and safety of tirzepatide in adults with obesity or type 2 diabetes, compared to placebo, GLP-1 receptor agonists (GLP-1 RAs), and insulin. Method: PubMed, Embase, and the Cochrane Library were searched on 17 January 2024, focusing on phase II and III randomized controlled trials (RCTs). We included studies involving adults with T2D or obesity, comparing tirzepatide to placebo, GLP-1 RAs, or insulin. The primary outcomes were the proportion of participants achieving ≥5%, ≥10%, and ≥15% weight loss targets. Secondary outcomes included changes in body weight, waist circumference, HbA1c levels, and blood pressure. Safety outcomes focused on adverse event rates. Meta-analyses were performed, and risk of bias was assessed using the Cochrane Risk-of-Bias tool version 2. Results: Fourteen RCTs involving 14,713 patients were included. Tirzepatide significantly increased the proportion of participants achieving weight loss targets, and reduced body weight, waist circumference, HbA1c, and blood pressure versus placebo and insulin. Compared with GLP-1 RAs, tirzepatide provided comparable or better outcomes in weight loss, waist circumference, and glycemic control. The incidence of gastrointestinal adverse events was significantly higher at all doses of tirzepatide compared to placebo and insulin. When compared with GLP-1 RAs, higher doses of tirzepatide were associated with increased risk of nausea, diarrhea, and decreased appetite, but not vomiting. Conclusions: Tirzepatide is an effective option for managing weight and improving metabolic outcomes in patients with T2D or obesity. However, it is associated with an increased risk of gastrointestinal adverse events, especially at higher doses. Therefore, close monitoring should be considered in clinical practice. Registration: PROSPERO CRD42021283449.